An up-scalable and cost-effective methodology for isolating a polypeptide matrix metalloproteinase-9 inhibitor from Lupinus albus seeds - Mota, Joana (2021)
One of the most challenging problems with food-borne bioactive compounds is that there are commonly no cost-effective, generally recognized as safe (GRAS) methods for obtaining gram quantities of their purified forms. Here we aimed at developing a method to isolate deflamin, an oligomeric protein from lupin seeds with anti-inflammatory and anticancer activity through matrix metalloprotease (MMP)-9 inhibition. Our goal was to develop a GRAS method that could be easily up-scalable whilst maintaining deflamin’s activity. A sequential precipitation methodology was developed, using an aqueous extraction, followed by heat denaturation, acid precipitation and solubilization in ethanol. A final precipitation with 90% ethanol yielded a purified protein which was sequenced through mass spectrometry and tested for its MMP inhibitory activity using the Dyequenched (DQ) gelatin assay and the standard wound healing assay in HT29 cells. The developed method yielded a purified oligomer, which represented 0.1% (w/w) of total dry seed weight and was positively confirmed to be deflamin. It further showed to effectively reduce MMP-9 gelatinolytic activity as well as colon cancer cell migration, hence corroborating the effectiveness of our method. Overall, this is the first reported method for isolating an MMP-9 inhibitor from legume seeds, which is up-scalable to an industrial level, in a cost-effective manner